2010
DOI: 10.1007/s12272-010-0815-z
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of the novel Na+/H+ exchanger-1 inhibitor KR-32560 in a perfused rat heart model of global ischemia and reperfusion: Involvement of the Akt-GSK-3β cell survival pathway and antioxidant enzyme

Abstract: To investigate the cardioprotective effects and mechanism of action of KR-32560 {[5-(2-methoxy-5-fluorophenyl)furan-2-ylcarbonyl]guanidine}, a newly synthesized NHE-1 inhibitor, we evaluated the effects of KR-32560 on cardiac function in a rat model of ischemia/reperfusion (I/R)-induced heart injury as well as the role antioxidant enzymes and pro-survival proteins play these observed effects. In isolated rat hearts subjected to 25 min of global ischemia followed by 30 min of reperfusion, KR-32560 (3 and 10 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
4

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 63 publications
0
6
0
4
Order By: Relevance
“…In addition to Akt activation, Yao et al (2010) found H 2 S inhibited GSK3␤ and subsequently inhibited the opening of mitochondrial permeability transition pore (mPTP). NHE-1 inhibition was also noted to produce cardioprotection via the phosphorylation and inhibition of GSK3␤ (Jung et al, 2010). These findings suggest that H 2 S may inhibit GSK3␤ through the inhibition of NHE-1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to Akt activation, Yao et al (2010) found H 2 S inhibited GSK3␤ and subsequently inhibited the opening of mitochondrial permeability transition pore (mPTP). NHE-1 inhibition was also noted to produce cardioprotection via the phosphorylation and inhibition of GSK3␤ (Jung et al, 2010). These findings suggest that H 2 S may inhibit GSK3␤ through the inhibition of NHE-1 activity.…”
Section: Discussionmentioning
confidence: 99%
“…*P Ͻ 0.05 vs. WT; #P Ͻ 0.05 vs. S571E. (27). Investigation of the upregulation of phosphorylated Na v 1.5 at shorter and multiple time points for I/R would help elucidate the role of I Na,L in mechanisms of Na ϩ overload and how it relates to changes in phosphorylated CaMKII and other Ca 2ϩ -handling proteins.…”
Section: Discussionmentioning
confidence: 99%
“…One particularly important protective mechanism involves attenuation of oxidative stress. 51,52 Reactive oxygen species (ROS) stimulate upstream kinases that activate NHE1 and increase intracellular Ca 2þ levels; 53 both ROS and increased Ca 2þ regulate opening of the mitochondrial permeability transition pore, a key contributor to ischemiareperfusion injury. [54][55][56][57] The NHE1 blockers and IC both reduce production of ROS 58,59 ; NHE1 blockers also preserve mitochondrial integrity during ischemia.…”
Section: Implication Of Nhe1 In Ischemia-reperfusion Injurymentioning
confidence: 99%